2018
DOI: 10.1111/sltb.12496
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Stigma and Suicide Literacy in a Clinical Sample

Abstract: Given the low levels of suicide literacy in this clinical sample, suicide prevention initiatives designed for community settings may also be important in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
2
13
1
5
Order By: Relevance
“…Increasing mental health literacy could be helpful to tackle the stigma associated with sensitive topics such as depression, low self-esteem, and self-harming thoughts or behavior. [ 69 70 ] Public health educators would specifically need to target the young population, to provide knowledge on identifying the early patterns, and to eventually promote help-seeking from mental health professionals. As a recent study found academic pressure to be one of the greatest factors for suicide risk in adolescents,[ 71 ] this could be addressed by the educational system by redesigning academic structures to minimize such pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing mental health literacy could be helpful to tackle the stigma associated with sensitive topics such as depression, low self-esteem, and self-harming thoughts or behavior. [ 69 70 ] Public health educators would specifically need to target the young population, to provide knowledge on identifying the early patterns, and to eventually promote help-seeking from mental health professionals. As a recent study found academic pressure to be one of the greatest factors for suicide risk in adolescents,[ 71 ] this could be addressed by the educational system by redesigning academic structures to minimize such pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Die Items luden in dieser Stichprobe mit 0,67-0,83 auf den Faktoren. Die Faktorladungen waren im Vergleich zu anderen Validierungsstudien des SOSS ähnlich hoch [14][15][16]. Die Faktoren erklärten insgesamt 59,4 % der Gesamtvarianz [11].…”
Section: Die Stigma Of Suicide Scale (Soss)unclassified
“…Die Faktoren erklärten insgesamt 59,4 % der Gesamtvarianz [11]. Andere internationale Validierungsstudien des SOSS erzielten niedrigere beziehungsweise ähnlich hohe Werte [14][15][16].…”
Section: Die Stigma Of Suicide Scale (Soss)unclassified
“…Интернет-психообразование направлено на дестигматизацию («дедемонизацию») психических расстройств и сопряженного СП, улучшая доступность антикризисной помощи [79,80]. Школьные программы следует направить на адекватное реагирование на стрессогенные посты в социальных сетях и «цифровое гражданство» [81][82][83].…”
unclassified
“…Internet psycho-education is aimed at destigmatization ("de-demonization") of mental disorders and associated SB, improving the availability of anti-crisis assistance [79,80]. School programs should be directed to an adequate response to stressful posts on social networks and "digital citizenship" [81][82][83].…”
mentioning
confidence: 99%